Poem O My Grieved Heart - Hamad Ghadeer, Amer (International Journal of Psychosocial Rehabilitation, 2020)
This paper examines the /l/ rhymed poem of Muhammed Bahga Al-Athari. It is an elegy, mourning his deceased instructor (sheikh) Mahmoud Shukri Al-Alusi. This study is divided into two sections. In the first section, the biographies of both Muhammed Bahga Al-Athari and his instructor (Sheik Mahmoud Shukri Al-Alusi) are introduced. The second section tackles some rhetorical features and explains some ambiguous words included in the poem.